Regulation of Anti-Angiogenic Pedf Through a TSP-1 - CD36 Pathway in Prostate Cancer - (:unkn) unknown (My University, 2013)
Prostate cancer (PCa) is the most common type of cancer diagnosed in American men. Cancer progression is associated with increased angiogenesis, and thrombospondin-1 (TSP–1) and pigment epithelium derived factor (PEDF), both potent anti-angiogenic molecules, are downregulated in PCa cells. TSP-1 exerts its activity through binding to several cell surface receptors such as CD36. Both TSP-1 and PEDF are multi-functional proteins and have been linked to lipid metabolism in other cell types. Moreover, TSP-1 - PEDF regulatory loops have been identified in some cell types. PEDF has been shown to inhibit PCa growth through its effects on angiogenesis and directly on the PCa cells; however, how PEDF expression levels are regulated in prostate cells is currently unknown. Here, we hypothesized that TSP-1 may regulate PEDF expression and lipid metabolism in PCa cells. I collected and examined PEDF levels in both cell lysate and serum-free conditioned media samples from TSP-1 and anti-CD36 antibody treated prostate cells and examined PEDF levels. Both TSP-1 and anti-CD36 treatment increased PEDF expression in normal prostate epithelial cells, RWPE-1, and in PCa cells, PC-3 and LNCaP. The expression of candidate TSP-1 - CD36 signaling mediators, fyn, p38 MAPK and JNK, were also examined in treated samples. I found that TSP-1 treatment elevated expression of fyn, p38 and JNK in PC-3 and DU145 cells. In contrast, blocking the CD36 receptor diminished the expression of each signaling mediator. My results are the first to show that a regulatory loop exists between TSP-1 and PEDF in prostate cells. The observation that treatment with anti-CD36 antibody also increased PEDF suggests that TSP-1 regulation of PEDF may be mediated through the CD36 receptor. These observations suggest that one mechanism of PEDF down-regulation in PCa cells may be due to loss of TSP-1 expression. Moreover, this pathway could be exploited for novel therapeutic interventions.